Legal analysis of Niet Onvankelijke Verklard's Decision (NO) on the application for announcement of marriage a TNI soldier who forged a marriage license (Case Study of Cilacap Religious Court Decision Number: 0922/Pdt.G/2021/PA.Clp) - Hamid Hamid (Annals of Justice and Humanity, 2024)
Purpose: This study aims to analyze the application of law to the administrative requirements of a Marriage License (SIN) that is formally flawed and the implications of the Niet Onvankelijke Verklaard (NO) decision on the marriage of a TNI soldier who falsified the Marriage License (SIN). Research methodology: The method in this study is written in a Normative Juridical manner, is descriptive analytical, the legal material is with secondary data that includes related laws and books. Results: The results of the study state that the application of the provisions in Article 72 paragraph (2) of the Compilation of Islamic Law which regulates the provisions for the annulment of a marriage carried out with the condition of "Fraud" can be used as a basis for a judge to annul the marriage so that justice can be realized for the Applicant and Respondent. Meanwhile, the legal implications of the Niet Onvankelijke Verklaard (NO) decision are that the marriage and children born are still considered valid and remain recorded because they have legal force, but there are also losses incurred for the wife and children in terms of official care and losses for the TNI institution and the Marriage Registration Agency or the Office of Religious Affairs (KUA).